Apical transportation of nickel titianium reciprocating instruments. An in vitro study - Dario Di Nardo; Massimo Galli; Morgana Foghetti; Almira Isufi; Ivana Vidovic; Tugba Turk; Gabriele Miccoli (Annali di Stomatologia)
Introduction: The introduction of Nickel-Titanium (NiTi) has revolutionized the field of endodontics. This alloy allows for easy navigation of the canal curvatures, enabling more conservative root canal preparations in a significantly reduced time. This capability stems from superelasticity, a property that enables NiTi to flex and adapt to the canal’s shape. Superelasticity allows the instrument to maintain a centered position even in the presence of pronounced curvatures, minimizing the restoring force typical of steel instruments and reducing negative effects, such as perforations, stripping, and blockages, on the canal’s original trajectory. Aim of this study is to evaluate the transportantion tendency of NiTi instruments in vitro. Materials and methods: Fifteen EndoTraining Blocks were divided into three groups of five blocks each: Group A was treated using WaveOne # 25.08 files; Group B was shaped with Reciproc #25.08 instruments; and Group C was shaped using TF Adaptive #25.08 files. All groups were reamed to a working length of 18 mm without the use of lubricants, following the establishment of a glide path with a #15.02 k-file. The instruments w ere utilized in a “ back and forth” motion, applying very light pressure and cleaning the coils of debris after each movement. The WaveOne and Reciproc reciprocating instruments were mounted on a 6:1 reduction handpiece controlled by a torque-controlled motor (Silver Reciproc VDW), using the pre-set programs WaveOne ALL for Group A and Reciproc ALL for Group B, respectively. The blocks in Group C were prepared with an Elements Adaptive engine set to the dedicated program for TF Adaptive. Results: All the external sides of the blocks registered statistically significant different apical transportation amongst groups (p<0.05). No statistical differences were found between the WaveOne and TF Adaptive groups regarding internal and external cutting surfaces at the apical third (p>0.05). Statistically significative differences were found between internal and external sides of the Reciproc’s blocks (p<0.05). Conclusions: From the examination of the data obtained in this experimental thesis, we conclude that all three types of instruments analyzed can lead to alterations in the original anatomy when operated inside a curved canal. Reciproc and WaveOne instruments demonstrated a significant tendency for canal transport, while the TF Adaptive system, exhibited superior maintenance of the original anatomy in both the coronal and more delicate apical regions.